Práticas corporais de matriz africana na educação física: o corpo como arquivo vivo da ancestralidade - Vieira, Ronaldo Ulisses (Universidade Federal de São Carlos, 2026)
This research presented an intervention proposal aimed at integrating the African matrix into Physical Education classes, highlighting its importance within the thematic units of dance, games, and combat activities. The proposal sought to contribute to the strengthening and expansion of existing methodologies for working with these cultural manifestations in the context of school pedagogy, supporting practices that still prove limited in light of the complexity and diversity of these cultural expressions. In this regard, the study is aligned with the BNCC, the DCNERER (2004), Laws No. 10.639/2003 and No. 11.645/2008, and the pedagogical guidelines of the municipality of Sorocaba, São Paulo, with the aim of supporting pedagogical practice geared toward multicultural education and awareness of ethnic-racial relations. The research was conducted with a 4th-grade class in the early years of elementary school at a municipal public school in Sorocaba, São Paulo, under the direct involvement of the teacher-researcher himself. The methodology adopted was qualitative in nature, drawing on interpretive anthropology, through which cultural phenomena were understood based on the interpretation of the meanings attributed by the subjects involved. Data were collected through field notes and audiovisual records in order to capture the experiences, perceptions, and interactions that emerged throughout the 16 classes of the didactic unit. The analytical categories mobilized were body and ancestry, examined in dialogue with Bodily Culture and African Matrices (CCMA), African Ontological Foundations (FOA), and the theoretical-methodological propositions of Pretagogia. The results showed that the students understood the classes as components of Afro-Brazilian culture, recognizing bodily practices as legitimate cultural productions, while also demonstrating greater engagement in the activities carried out. It is noteworthy that the notion of quilombo proved to be of central importance to learning, and that the participation of quilombola groups in the process significantly contributed to understanding the historical, social, and cultural dimensions of this tradition, broadening reflection on resistance, ancestry, and belonging. Thus, the didactic unit made relevant contributions both to the students’ cultural education and to the improvement of future pedagogical practices in Physical Education. As an educational resource, an e-book was developed featuring a board game inspired by African matrix bodily practices, based on the triad of dance, games, and combat activities addressed throughout the educational process.
African-based body practices in physical education: the body as a living archive of ancestry
Keywords: Ancestralidade; Corpo; Educação física escolar; Matriz africana; Quilombo; Ancestry; Body; School physical education; African matrix; Quilombo; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 18. Igualdade Étnico-Racial para o Desenvolvimento Sustentável; 4. Educação de Qualidade; 10. Redução das Desigualdades